2022
DOI: 10.1002/adfm.202205771
|View full text |Cite
|
Sign up to set email alerts
|

Stable Imprinted Zincophilic Zn Anodes with High Capacity

Abstract: Stable Zn anode capable of working at high currents and high capacities remains a great challenge. Although construction of 3D Zn frameworks can achieve improved cycling properties to some extent, they are usually combined with low energy density, complex fabrication process, and high cost. Herein, a zincophilic Zn foil with 3D micropatterns utilizing a simple and scalable imprinting strategy with predesigned mold by femtosecond laser is reported. The imprinting induced microchannels with enhanced Zn 2+ affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…As a promising reliable alternative, rechargeable aqueous zinc-ion batteries have multiple advantages by using Zn anodes, such as high safety, rich natural resources, and high theoretical capacity (820 mAh g −1 and 5855 mAh cm −3 ) [5][6][7] . However, Zn anodes suffer from poor plating/ stripping reversibility and notorious dendrite growth, which results in unsatisfactory cycling stability [8][9][10][11][12] . In addition, Zn anodes also face problems by side reactions and corrosions in aqueous electrolytes [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…As a promising reliable alternative, rechargeable aqueous zinc-ion batteries have multiple advantages by using Zn anodes, such as high safety, rich natural resources, and high theoretical capacity (820 mAh g −1 and 5855 mAh cm −3 ) [5][6][7] . However, Zn anodes suffer from poor plating/ stripping reversibility and notorious dendrite growth, which results in unsatisfactory cycling stability [8][9][10][11][12] . In addition, Zn anodes also face problems by side reactions and corrosions in aqueous electrolytes [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…We synthesize three samples to investigate the influence of the structure and zincophilic degree on the performance: a highly zincophilic 2DZS, a highly zincophilic 3D zincophilic sieve (3DZS), and a relatively zincophobic 2D TiO 2 (2DTO) with a similar 2D mesoporous structure to 2DZS. , To investigate the formation mechanism of 2DZS (Scheme ), a series of ex situ morphologic studies are conducted as shown in Figure S2–6. First, the pre-precipitation of ZnS is inhibited via the acid-assisted strategy: HOAc is used to coordinate F127 and ZnS to form a mono-precursor, , and hydrochloric acid (HCl) is the pH regulator to control the precipitation kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…The rate performance measurement shows that Zn-GZH can possess a lower and more stable voltage hysteresis at currents ranging from 0.5 to 20 mA cm –2 (Figure S19e). The electrochemical performance of Zn-GZH is superior to the recently reported Zn protective layers under mildly acidic conditions (Figure g). ,,,, According to the previous analyses, the improvement of electrode stability by the dielectric–metallic ultrathin film can be attributed to the intrinsic high permittivity, high breakdown voltage, and good interfacial compatibility, which can effectively block the electron pathways, reduce side reactions, and further ensure electrochemical reversibility …”
mentioning
confidence: 78%